Screening for Autism Spectrum Disorder in Children up to Age 2.5 years in a Tertiary Care Hospital - Anum Farooq; Shoaib Ahmed (Life and Science)
Objective: To investigate the frequency of Autistic Spectrum Disorder (ASD) by screening 16 to 30 months old children, reporting to a tertiary care hospital. Study Design: Cross sectional study. Place and Duration of Study: The study was conducted in the Paediatrics Outpatient Department of Military Hospital, Rawalpindi from November 2017 to August 2018. Materials and Methods: A total of 163 children between the age of 16-30 months were screened using Urdu translated version of Modified Checklist for Autism in Toddlers, revised with Follow-Up (M-CHAT-R/FTM). Those who screened positive on MCHAT-R were assessed using Childhood Autism Rating Scale-2 (CARS 2) and Diagnostic and Statistical Manual-5 (DSM-5) as diagnostic tools. Results: Among the 163 children screened with MCHAT, 33 were found positive for autism. The positive individuals were further assessed on CARS-2 and DSM-5; five children were diagnosed with ASD at moderate to severe level.  This study has shown that 3% of children visiting the hospital for various reasons suffer from ASD. Conclusion: This study concluded that 3% of the children coming to the hospital for any purpose were found to have ASD. There is a need to make Level 1 screening an essential part of regular check-ups of children in Paediatrics outpatient clinics.